CENTRALIZED PURCHASING IN HEALTH - Jorge Aperta; Andrea Borges; Diana Cadilha; Francisca Dimas; Cristina Dinis; José Feio; Olímpia Fonseca; Martinha Garcia8; Filomena Marques; João Ribeiro; Celina Rodrigues; Cláudia Santos; et al. (Formifarma, LDA., 2015)
The centralization of purchases has been increasingly a strategic trend, particularly in the health sector. In Portugal, the SPMS, Serviços Partilhados do Ministério da Saúde, E.P.E., was established in 2010 as a central purchasing entity for the health sector. Centralized purchasing can bring advantages, such as increasing the efficiency of the purchasing process, but also disadvantages, such as the possibility of oligopoly by suppliers, generated by imperfect competition, and a diminished response to the most decentralized units. This theme was the subject of a reflection meeting, which aimed to promote a debate on the national framework aspects of this process, challenges of implementation for hospital medicines and suggestions for improvement of this process. The main ideas generated for a successful centralized purchasing indicate that the central purchasing entity should be dynamic and facilitator, should ensuring equity, safety, accessibility and quality of drugs. There should be better planning and rigorous procurement of drugs, and an integrated information system that allows sharing and networking among the central purchasing and the various health institutions, fostering a proximity policy, should be created. Professionals should be trained in the necessary technical procedures for the completion of the acquisition of drugs, and hospital pharmacists should be included as consultants in the development of specific procedures of centralized procurement, according to the hospital's needs. Finally, this entire process must be followed by constant monitoring through an annual assessment of the economic and financial feasibility. The benefits of the activity performed annually should adequately quantify the quality and efficiency gains that demonstrate the financial impact achieved in scope of the reduction of expense in the National Health Service.